2016
DOI: 10.1002/ese3.109
|View full text |Cite
|
Sign up to set email alerts
|

Study of thermal behavior of deoiled karanja seed cake biomass: thermogravimetric analysis and pyrolysis kinetics

Abstract: Karanja is a medium sized evergreen tree which has minor economic importance in India. The nonedible seed kernel contains 27-30% oil that is used for biodiesel production, leaving the remaining nonedible seed cake as a waste product. The aim of the present work was to obtain kinetic parameters in relation to technological parameters in nonedible seed cake biomass pyrolysis conversion process to bio-oil and biochar. Effects of heating rate on karanja seed cake slow pyrolysis behavior and kinetic parameters were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Activation energy values are found to be 51.26, 51.63 and 53.60 KJ/mol and frequency factor values are found to be 2650, 7070 and 7480 min -1 at three heating rates of 10, 20 and 30 K min -1 respectively. Both the kinetic parameters, Activation energy, and frequency factor were increased with heating rate and the same trend is observed in the literature [15]. The obtained TGA data were also analyzed using iso-conversion methods such as Kissinger-Akahira-Sunose (KAS) method and Flynn-Wall-Ozawa (FWO) method and the regression lines for different conversion values at three individual heating rates of 10, 20, 30 K min -1 are displayed in Figure 6a and 6b respectively.…”
supporting
confidence: 87%
“…Activation energy values are found to be 51.26, 51.63 and 53.60 KJ/mol and frequency factor values are found to be 2650, 7070 and 7480 min -1 at three heating rates of 10, 20 and 30 K min -1 respectively. Both the kinetic parameters, Activation energy, and frequency factor were increased with heating rate and the same trend is observed in the literature [15]. The obtained TGA data were also analyzed using iso-conversion methods such as Kissinger-Akahira-Sunose (KAS) method and Flynn-Wall-Ozawa (FWO) method and the regression lines for different conversion values at three individual heating rates of 10, 20, 30 K min -1 are displayed in Figure 6a and 6b respectively.…”
supporting
confidence: 87%
“…Previous literature has been published on the estimation of kinetic parameters of biomass degradation to biochar using the model‐free method . Huang et al investigated the pyrolysis kinetics of soybean straw using the KAS and FWO methods in an inert Argon atmosphere and reported that, initially, E a increased smoothly as the conversion increased from 0.1 to 0.3, and then it maintained a constant trend until 0.6 and decreased drastically from 176 to ∼50 kJ/mol as the conversion increased from 0.6 to 0.7.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this was the involvement of multistep reactions instead of the single step reaction mechanism for the decomposition of biomass. Muktham et al studied the thermal behaviour of de‐oiled karanja seed cake biomass using model‐free thermogravimetric analysis. They found that E a decreased with an increase in conversion, as high conversion was observed at high temperature, and the energy required at elevated temperatures was lower than at lower temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Since the wood contained higher moisture contents (8 %) than the DIS (< 2 %), the loss of water is noticeable in the DTG curve. The major mass loss occurred between 225 and 400 °C with the decomposition of cellulose, hemicellulose, and lignin 29, 30. The wood consists of a negligible fraction of ash, so no decomposition of minerals occurred at higher temperatures > 600 °C.…”
Section: Resultsmentioning
confidence: 99%